2012
DOI: 10.1007/s10616-012-9454-1
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies on chemoprotective effect of borax against aflatoxin B1-induced genetic damage in human lymphocytes

Abstract: A common dietary contaminant, aflatoxin B1 (AFB1), has been shown to be a potent mutagen and carcinogen in humans and many animal species. Since the eradication of AFB1 contamination in agricultural products has been rare, the use of natural or synthetic free radical scavengers could be a potential chemopreventive strategy. Boron compounds like borax (BX) and boric acid are the major components of industry and their antioxidant role has recently been reported. In the present report, we evaluated the capability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Recent investigations have focused on therapeutic substances capable of reducing the genotoxicity or carcinogenicity of various natural and man-made mutagens. These substances include antibodies, fatty acids, amino acids, minerals, plant extracts, phenolic compounds, and boron compounds such as boric acid and borax (20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…Recent investigations have focused on therapeutic substances capable of reducing the genotoxicity or carcinogenicity of various natural and man-made mutagens. These substances include antibodies, fatty acids, amino acids, minerals, plant extracts, phenolic compounds, and boron compounds such as boric acid and borax (20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%
“…They showed that the used boron compounds were nontoxic (21). Moreover, negative results in a large number of mutagenicity assays exhibited that boron compounds especially boric acid and borax were non-genotoxic (41)(42)(43). In brief, the tested three compounds were found to have cytotoxic but not genotoxic damage potentials at increasing concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…AFB1 concentrations as low as 5 μM were shown to be effective at stimulating the formation of reciprocal translocations, and the karyotypes were confirmed by pulse field gel electrophoresis [103]. AFB1 is also a recombinagen in human and Chinese hamster ovary (CHO) cells and can increase the frequencies of SCE [104][105][106][107]. It is unclear whether the same AFB1-associated DNA lesions can stimulate both mutations and recombination.…”
Section: Afb1 Is a Potent Recombinagenmentioning
confidence: 99%
“…AFB1-associated SCE are also observed in human and mammalian cells. SCEs have been detected in human lymphocytes, Chinese hamster V79 cells, rat and mouse hepatocyte cell lines [104][105][106][107]. It has not yet been determined whether mammalian cells defective in homologous recombination exhibit more AFB1associated mutations.…”
Section: Template-switch Mechanisms As An Alternative Mechanism For Tmentioning
confidence: 99%